Unified Approach to Trajectory Data Mining and Multi-Aspect Trajectory Analysis with MAT-Tools Framework - Portela, Tarlis Tortelli; Machado, Vanessa Lago; Renso, Chiara (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2024)
Multiple-aspect trajectory (MAT) data mining requires sophisticated tools to handle the complexity and volume of complex data. This paper introduces MAT-Tools, a comprehensive Python framework for MAT data mining. The framework consists of five main packages: mat-data, which supports data preprocessing and synthetic dataset generation; mat-model, offering model classes tailored for MAT data; mat-similarity, providing methods for similarity measurement; mat-view, visualization tools for MAT data, experimental preparation, and results exploration on a web interface; and mat-classification and mat-clustering, which includes advanced classification and clustering algorithms. Each package addresses specific challenges in MAT data analysis, from preprocessing to modeling and classification. MAT-Tools facilitates efficient and accurate trajectory data analysis, making it invaluable for diverse tasks since exploratory data analysis, anomaly detection, and predictive modeling applications. This framework's integration and extensibility empower researchers and practitioners to gain deeper insights and achieve more reliable results in trajectory data mining.